Analysis of reported cases of repeated violence in Espírito Santo - Franciéle Marabotti Costa Leite; Gabriela Ravete Cavalcante; Marieli Thomazini Piske Garcia; Elisa Aparecida Gomes de Souza; Márcia Regina de Oliveira Pedroso; Bruna Venturin (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objectives: Identify the frequency of recurrent violence in cases reported in Espírito Santo and the associated factors. Methods: Cross-sectional study. Which included data on violence in Espírito Santo from 2011 to 2018, from the Notifiable Diseases Information System, and, Statistical analyzes were performed using the chi-square test and Poisson regression. Results: 54.2% (N:14.966) of reported cases of violence are repeated, and higher prevalences were associated with female sex (PR:1.54), child (PR: 1.29) or elderly victims (PR: 1.25), the presence of disabilities/disorders (PR:1.42) and occurrence in urban/peri-urban areas (PR: 1.10). Furthermore, there is a greater frequency of injuries caused by a single aggressor (PR: 1.20), man (PR: 1.28), aged 25 or over (PR: 1.09), known to the victim (PR: 2.81) and at home (PR: 1.69). Conclusion: The reported cases of violence showed a high frequency of recurrence, and were associated with the studied characteristics of the victim, the aggressor and the event.